Comparisons of Tensile Fracturing Behaviors of Hydraulic Fully Graded and Wet-Screened Concretes: A Mesoscale Study - Lei Xu; Yongmiao Jin; Shuaizhao Jing; Jie Liu; Yefei Huang; Changqiao Zhou (Advances in Materials Science and Engineering)
The widely used wet-screening method in the experimental testing of hydraulic fully graded concrete inevitably results in a gap between the real mechanical parameters of hydraulic fully graded concrete specimens and those of the corresponding wet-screened specimens and therefore necessitates the comparative study on their mechanical behaviors. To this end, a two-dimensional mesoscale modeling methodology is developed for simulating the tensile fracturing behaviors of hydraulic fully graded and wet-screened concretes, and extensive Monte Carlo simulations are performed. The individual effects of specimen size variation, variation of gradation and volume fraction of coarse aggregates, and the weaker interfacial transition zones surrounding the large coarse aggregates to be removed by wet-screening are detailed followed by the discussion on the combined effect of these three main factors. All the mean values of the macroscopic mechanical parameters related to tensile fracturing behaviors are found to show significant change in response to wet-screening, and the underlying differentiation mechanism and governing factor(s) are identified. Furthermore, it is shown that the randomness of the investigated parameters can be roughly described by the Gaussian distribution, and the dispersion of each of the investigated parameters of hydraulic fully graded concrete is higher than that of the corresponding wet-screened concrete.